Efeitos da atividade física regular no modelo animal de dor muscular crônica difusa e na ativação de neurônios corticais e da amigdala em camundongos - Oliveira, Larissa Resende (2017)
Chronic muscle widespread pain (CMWP) is a public health problem with high social and economic burden and appears to be related with changes in the functioning of cortical areas of the central nervous system. Physical activity, if practiced regularly, can benefit people with CMWP, and possibly prevent its development. Thus, the present study aimed to evaluate the effect of regular physical activity on the treatment and prevention of hyperalgesia on an animal model of CMWP as well as on the expression of cortical neurons. Seventy-nine male and female C57BL/6 mice (25-30 g) were housed separately in their home cages with free access to the running wheel, water and food (physically active animals) or only with water and food (sedentary animals). For induction of CMWP, animals received two intramuscular injections of pH 4.0 saline solution. We tested the mechanical hyperalgesia of the gastrocnemius muscle (Tweezer), and of the paw (von Frey filaments). The experimental design was divided into 4 protocols, with their respective groups: 1) 2 weeks of physical activity after induction of hyperalgesia, with groups of physically active animals (n = 8) and sedentary animals (n = 8) ); 2) 2 weeks of physical activity prior to induction of hyperalgesia, with healthy and physically active animals (AFP2) (n = 8) and the healthy and sedentary group (SDP2) (n = 8); 3) 2 weeks of physical activity after induction of hyperalgesia + additional exercise, with the group of animals physically active (AFT + EA) (n = 8) and sedentary animals (SDT + EA) (n = 8) and 4 weeks of physical activity before the induction of hyperalgesia, with the healthy and physically active group (AFP4) (n = 14) and healthy and sedentary (SDP4) (n = 14). Behavioral tests were performed at the following times: before and after induction of hyperalgesia, and after 48h, 96h, 1 week and 2 weeks of exercise (for protocols 1 and 2) and before and after 2 or 4 weeks of exercise, and during 1 week post exercise (for protocols 3 and 4). In order to evaluate the mechanisms of action of the exercise in the prevention of hyperalgesia, double immunofluorescence for cAMP (CREB) and phosphorylated CREB response element (pCREB) was used to label neurons in the following cerebral areas: anterior cingulate cortex ), insular cortex (IC), and central amygdala (ACe). The results showed that 2 weeks of voluntary physical activity or 2 weeks of voluntary physical activity + additional exercise did not revert the primary or secondary hyperalgesia of the CMWP model. However, 2 or 4 weeks of voluntary physical activity significantly prevented the increase of paw responses (bilateral hyperalgesia) bilaterally (p<0.05) in the animals of the AFP2 and AFP4 groups, and maintained this response by up to 4 (AFP2) or 5 Day (AFP4) after model induction (p<0.05), compared to the groups (SDP2) and (SDP4), respectively. In addition, a number of neurons were positively labeled for CREB and pCREB significantly lower in the AFP4 group when compared to the SDP4 group, in the following captured areas: CCA (p<0.0001), CI (p<0.0001), and ACe (p = 0.0007). Our findings indicate that short-term physical activity is not effective in the treatment of CMWP. However, regular physical activity is effective to prevent the increase of hyperalgesia, showing that physical inactivity is a risk factor for its development, and that changes in the sensory cortical neurons activity may be, at least in part, responsible for these results.